TRAITS EVALUATION FOR SOME F2 HYBRIDS IN TOMATO (Mesopotamia Journal of Agriculture)
This study comprised 20 F2-hybrids of tomato arranged in RCBD experiment with three replications to determine the most important traits which affect on tomato yield to be used as a selection index in tomato breeding programs. The studied traits were, number of fruits / plant, average fruit weight (g), early and total yield (kg/plant), plant height (cm) and number of branches per plant. The results showed existence of variation in most yield components, vegetative and qualitative studied traits. The total yield /plant had a highly positive and significant correlation with each of the early yield, average fruit weight. Which had positive direct effects on the total yield. whereas, the early yield had positive indirect effects on the tomato plant yield through fruit weight, no. of branches /plant and no. of fruits /plant